Handbook of small modular nuclear reactors - Carelli, Mario D.; Ingersoll, D. T.; ScienceDirect eBooks (Oxford : Woodhead Publishing, 2014)
Small modular reactors (SMRs) are an advanced, safe type of nuclear reactor technology that are suitable for small and medium sized applications including both power and heat generation. In particular, their use as individual units or in combination to scale-up capacity offer benefits in terms of siting, installation, operation, lifecycle and economics in comparison to the development of larger nuclear plant for centralised electricity power grids. Interest has increased in the research and development of SMRs for both developing countries as well as such additional cogeneration options as industrial/chemical process heat, desalination and district heating, and hydrogen production. This book reviews key issues in their development as well as international R & D in the field.
7.5 Differences in the treatment of HSIs in the nuclear industry and other industries7.6 How to identify and select advanced HSIs: five dimensions; 7.7 Operational domains of HSIs; 7.8 HSI technology classification; 7.9 HSI architecture and functions; 7.10 Implementation and design strategies; 7.11 Future trends; 7.12 Conclusion; 8: Safety of integral pressurized-water reactors (iPWRs); 8.1 Introduction; 8.2 Approaches to safety: active, passive, inherent safety and safety-by-design; 8.3 Testing of small modular reactor (SMR) components and systems.
CIP data; resource not viewed.
Elsevier
Keywords: Nuclear reactors; Nuclear reactors; Electronic books